THE IMPACT OF THE POLICY ON RISING FUEL PRICES ON INCREASING POVERTY RATES IN INDONESIA - Sumantri, Ii (Ikatan Dosen Menulis, 2022)
The surge in world oil prices was caused by the impact of the war in Europe between Russia and Ukraine. As a result of this war impacted the increase in oil prices almost all over the world. The existence of a surge in world oil is considered to have a significant impact on economic conditions in Indonesia. From now on, referred to as BBM, the amount of subsidized fuel oil worth almost 520 trillion is very burdensome and drains the state budget. Hence, the government considers it very urgent to increase the price of subsidized and non-subsidized fuel. Carry out meticulous and accurate calculations in calculating the fuel price increases in the country. The increase in the impact of the fuel price increase will have implications for inflation, so in the end, it will also affect the number of poor people in Indonesia. This study aims to determine the impact of the policy of increasing fuel prices on increasing the number of poor people in Indonesia. This study uses a qualitative approach with a descriptive method. The results of the study show that the reason for the policy of increasing fuel prices is to reduce the world's supply of crude oil, which does not match supply and demand, also because the existing subsidies have not been well targeted, where these subsidies are enjoyed mainly by middle and upper-class people. As for the impact of the increase in fuel prices for the community, among others, the increase in the price of goods and services, increasing the fare of public transportation, raising the prices of nine basic needs, hampering the rate of economic growth and decreasing the number of unemployed. The government can take policies in response to the increase in fuel prices to control and stabilize the prices of basic needs, provide direct assistance to the underprivileged, increase fuel prices gradually and issue regulations that limit motor vehicle ownership.